Age at the onset of menopause and its influencing factors in Turkish women in a rural area - Pirincci, Edibe; Oguzoncul, Ayse Ferdane; Tasdemir, Rabia (Routledge Journals, Taylor & Francis Ltd, 2016)
This study was performed to identify menopausal age and its determining factors in women over 40 residing in the Dogubeyazit district of Agri, located in Eastern Turkey. This cross-sectional study was performed on a sample of 1,068 women, selected by simple random sampling among all district health center records of women aged 40 and greater, who were each attributed a random serial number. While 35.6% of the subjects had not yet reached menopause, 60.5% had entered it spontaneously and 3.9% surgically. Average age at spontaneous menopause was 47.4 +/- 3.7 years and that of surgical menopause 45.1 +/- 5.0. Age at marriage, age of last pregnancy, and the age of the subject's mother at menopause affected menopausal status. Identifying menopausal age and its determining factors may modify the menopausal status of women and their management of the perimenopausal period.
Keywords: Age at menopause; menarche; women